2021
DOI: 10.1001/jamadermatol.2020.4066
|View full text |Cite
|
Sign up to set email alerts
|

Cost Minimization Analysis of a Teledermatology Triage System in a Managed Care Setting

Abstract: TD) enables remote triage and management of dermatology patients. Previous analyses of TD systems have demonstrated improved access to care but an inconsistent fiscal impact.OBJECTIVE To compare the organizationwide cost of managing newly referred dermatology patients within a TD triage system vs a conventional dermatology care model at the Zuckerberg San Francisco General Hospital and Trauma Center (hereafter referred to as the ZSFG) in California. DESIGN, SETTING, AND PARTICIPANTSA retrospective cost minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…The findings from Modai et al 24 are in agreement with Pak et al, 25 who found that eHealth used in an asynchronous setting in dermatology was even more expensive than conventional dermatology when only direct costs were considered. In contrast, Zakaria et al 26 reported that the implementation of a teledermatology triage system within the dermatology department was associated with cost savings compared to a conventional dermatology care model. Nonetheless, the study was limited by not including the revenue generated from billing and the exclusion of costs associated with rent, utilities, and non-personnel overhead.…”
Section: Discussionmentioning
confidence: 94%
“…The findings from Modai et al 24 are in agreement with Pak et al, 25 who found that eHealth used in an asynchronous setting in dermatology was even more expensive than conventional dermatology when only direct costs were considered. In contrast, Zakaria et al 26 reported that the implementation of a teledermatology triage system within the dermatology department was associated with cost savings compared to a conventional dermatology care model. Nonetheless, the study was limited by not including the revenue generated from billing and the exclusion of costs associated with rent, utilities, and non-personnel overhead.…”
Section: Discussionmentioning
confidence: 94%
“…2,3 While the utility and cost-effectiveness of teledermatology in ambulatory care have been demonstrated, its role in inpatient dermatological care is less defined. 2,4 Nonetheless, a small prospective study proposed by Gabel et al showed that teledermatology in the inpatient setting might be an acceptable option for diagnosis, evaluation and management. 5 Singapore was one of the first countries to report imported COVID-19 cases in early 2020, with subsequent government public health measures to contain the spread.…”
Section: Early Experience Of Inpatient Teledermatology In Singapore During Covid-19mentioning
confidence: 99%
“…Provider cost savings may also be associated with increased use of telemedicine, though specific data in urology and TRT are lacking [ 22 ]. While the implementation of telemedicine can require initial capital investment from providers and practices, subsequent use of telemedicine can theoretically deliver long-term cost savings through decreased resource utilization.…”
Section: The Benefitsmentioning
confidence: 99%